Cardiorenal Protective Effect of Costunolide against Doxorubicin-Induced Toxicity in Rats by Modulating Oxidative Stress, Inflammation and Apoptosis - Xing, Wen; Wen, Chaoling; Wang, Deguo; Shao, Hui; Liu, Chunhong; He, Chunling; Olatunji, Opeyemi Joshua (Molecules (Basel, Switzerland), 2022)
Doxorubicin (DXB) is one of the most commonly used anticancer agents for treating solid and hematological malignancies; however, DXB-induced cardiorenal toxicity presents a limiting factor to its clinical usefulness in cancer patients. Costunolide (COST) is a naturally occurring sesquiterpene lactone with excellent anti-inflammatory, antioxidant and antiapoptotic properties. This study evaluated the effect of COST on DXB-induced cardiorenal toxicity in rats. Rats were orally treated with COST for 4 weeks and received weekly 5 mg/kg doses of DXB for three weeks. Cardiorenal biochemical biomarkers, lipid profile, oxidative stress, inflammatory cytokines, histological and immunohistochemical analyses were evaluated. DXB-treated rats displayed significantly increased levels of lipid profiles, markers of cardiorenal dysfunction (aspartate aminotransferase, creatine kinase, lactate dehydrogenase, troponin T, blood urea nitrogen, uric acid and creatinine). In addition, DXB markedly upregulated cardiorenal malondialdehyde, tumor necrosis factor-α, interleukin-1β, interleukin-6 levels and decreased glutathione, superoxide dismutase and catalase activities. COST treatment significantly attenuated the aforementioned alterations induced by DXB. Furthermore, histopathological and immunohistochemical analyses revealed that COST ameliorated the histopathological features and reduced p53 and myeloperoxidase expression in the treated rats. These results suggest that COST exhibits cardiorenal protective effects against DXB-induced injury presumably via suppression of oxidative stress, inflammation and apoptosis.